Komunikasi Secara Virtual Para Pemain MMORPG Ragnarok X: Next Generation - Yuli Purnamasari; Yuni Clara; Lady Yesisca; Frans Immanuel; Muhamad Isnaini (Jurnal Ilmiah Komunikasi (JIKOM) STIKOM IMA, 2023)
Virtual communication that occurs between Ragnarok X: Next Generation game players occurs when they are members of a guild. The diversity of cultures and social structures creates many communication gaps between players. This study aims to determine the process of virtual communication that occurs between different ROX players. This research uses the methodvirtual ethnography with a qualitative approach in reaching the world of online game players. The players communicate via WhatsApp and the Discord application, but the players don't talk about the technicalities of the game, they discuss things outside the game so there's no dispute. ROX players do not experience deindividuation such as loss of self-awareness, self-change where players distance themselves from the group. It can be concluded that not all online games have a bad impact on individuals depending on the individual's response to playing these online games. The suggestion from this research is that online game players don't experience deindividuation, they can focus ongame however, when in the real world the player becomes himself, not a character in the online game.